Beryllium‐Assisted p‐Type Doping for ZnO Homojunction Light‐Emitting Devices. (29th March 2016) - Chen, Anqi; Zhu, Hai; Wu, Yanyan; Chen, Mingming; Zhu, Yuan; Gui, Xuchun; Tang, Zikang
Abstract : A key step in realization of a ZnO homojunction light‐emitting diode is the effective p‐type doping in ZnO:N. In this article, a feasible route is demonstrated to enhance hole doping in ZnO:N films by the assistance of Beryllium. The newly synthesized p‐type ZnO is applied in light‐emitting devices. The corresponding p–i–n junction exhibits excellent diode characteristics, and strong near band edge ultraviolet emissions is also observed even at temperatures as high as 400 K under the injection of continuous current. The results represent a critical advance toward the development of high‐efficiency and stabilized p‐type ZnO, which is also a desirable key step for future ZnO‐based optoelectronic applications. Abstract : High performance ZnO‐based UV‐light‐emitting diodes are achieved by using a reliable route of p‐type doping ZnO through the Be‐assisted N‐acceptor complex doping method. The results represent a critical advance toward the development of highly efficient and stabilized p‐type ZnO, which is also a desirable key step for future ZnO‐based optoelectronic applications.